IMPLEMENTASI UU NO 40 TAHUN 2007, TENTANG COORPORATE SOCIAL RESPONBILITY CSR DALAM UPAYA UPT PERPUSTAKANSTIE PASAMAN MEMPEROLEH MANFAATNYA PADA 8 PERUSAHAAN DI KABUPATENPASAMAN BARAT - Nur Hamzah; Zuhafni ST Parpatiah (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2017)
This study was to observe how the implementation of Law Number 40 in 2007, on CSR as effort at UPT Library of STIE Pasaman, it was obtained benefit on 8 factories in West Pasaman. The populations in this study were 8 companies using survey technique as technique sampling. In this research found there were 3 companies that lees in implementing of CSR, 1 company was good, 2 companies were excellent and 2 companies were quite good in responding the implementation of CSR at UPT Library of STIE Pasaman. Keywords: CSR, Library, Education.